2014
DOI: 10.1007/s00464-014-3843-9
|View full text |Cite
|
Sign up to set email alerts
|

Imaging visceral adhesion to polymeric mesh using pneumoperitoneal-MRI in an experimental rat model

Abstract: T2-weighted pneumoperitoneal-MRI is a powerful tool for assessing adherence after intraperitoneal mesh implantation. According to the mini-invasive procedure adopted here, this approach may allow a temporal follow-up of adherence fate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Hooker et al 31 used an animal model for testing adhesion prevention strategies in IPOM surgery with local abrasion of small bowel. Other groups de-peritonealized the cecum to provoke adhesion formation after mesh implantation 32 , 33 . Since the small intestine and cecum are mobile in the peritoneal cavity, our model additionally places a suture from the cecal mesenterium to the abdominal wall to ensure that mesh and injured peritoneum of abraded cecum stay in contact postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Hooker et al 31 used an animal model for testing adhesion prevention strategies in IPOM surgery with local abrasion of small bowel. Other groups de-peritonealized the cecum to provoke adhesion formation after mesh implantation 32 , 33 . Since the small intestine and cecum are mobile in the peritoneal cavity, our model additionally places a suture from the cecal mesenterium to the abdominal wall to ensure that mesh and injured peritoneum of abraded cecum stay in contact postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The second type of mesh was a polyethylene terephthalate (PET) multifilament textile without barrier. The PET was used as a positive control for the development of soft tissue visceral attachment [12,15] to the mesh. Tissue attachments was induced , using a caecal abrasion and a peritoneal defect model previously described [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…A recent preclinical study showed that a collagen coated mesh can be imaged over time using Amide Proton transfer MRI [10]. Regarding abdominal adhesions to the mesh, Cine-MRI in humans [11] and in experimental rodents using pneumoperitoneal-MRI [12] was proven useful to document this side effect. Despite the large range of offered contrasts, the high spatial resolution and the absence of radiation exposure, MRI usually does not allow to easily image the meshes and remains an emerging technique for the exploration of VHR complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Was conducted macroscopic evaluation of the wounds considering presence or absence of the following parameters: hematoma, infection, wound dehiscence, fistula and adhesions. Regarding the adhesions, was used the parameters of Goncalves et al 3 , which classifies them in relation to the intensity (Chart 1).…”
Section: Macroscopic Healing Evaluationmentioning
confidence: 99%